2013
DOI: 10.1136/bmjopen-2013-003569
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren's syndrome 1976–2005 and associated interstitial lung disease: a population-based study of incidence and mortality

Abstract: ObjectiveA very few studies describe the epidemiology of primary Sjögren's syndrome (pSS). The reported frequency of pulmonary involvement in pSS varies widely depending on the detection method employed, and consists mainly of various forms of airways disease. We aimed to evaluate the incidence and mortality of pSS and of lung disease in pSS, focusing on interstitial lung disease (ILD).MethodsA population-based incidence cohort of patients diagnosed with pSS in 1976–2005 was assembled. Diagnosis was based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 25 publications
2
98
0
2
Order By: Relevance
“…pSS is a chronic autoimmune disease, and genetic predisposition may play a role in its pathogenesis (13). A population-based study showed that the annual incidence of pSS was 5.1/100,000 population, and increased with age at pSS diagnosis (18-44 years: 1.8/100,000 vs. ≥75 years: 10.7/100,000) (14). Female patients were more affected (8.7/100,000) than male patients (1.1/100,000) (14).…”
Section: Discussionmentioning
confidence: 99%
“…pSS is a chronic autoimmune disease, and genetic predisposition may play a role in its pathogenesis (13). A population-based study showed that the annual incidence of pSS was 5.1/100,000 population, and increased with age at pSS diagnosis (18-44 years: 1.8/100,000 vs. ≥75 years: 10.7/100,000) (14). Female patients were more affected (8.7/100,000) than male patients (1.1/100,000) (14).…”
Section: Discussionmentioning
confidence: 99%
“…The development of lung disease in pSS was associated with poor survival. 19 Thus, repeated pulmonary function tests and diagnostic radiology are necessary and should be the preferred methods to monitor pSS-specific organ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scan abnormalities are found in 34-50% of patients [38]. The annual incidence of respiratory manifestations is estimated at 10% (±3%) 1 year after diagnosis of Sjögren's syndrome and increases to 20% (±4%) by 5 years [6].…”
Section: Sjögren's Syndrome Patients With Pulmonary Involvementmentioning
confidence: 99%
“…Clubbing is rare [36]. ILD is associated with premature mortality [6]. The presence of anti-SSA is a predisposing factor of ILD [90].…”
Section: Ild In Sjögren's Syndromementioning
confidence: 99%
See 1 more Smart Citation